The C-terminus of NMDAR GluN1-1a Subunit Translocates to Nucleus and Regulates Synaptic Function - Zhou, Liang; Duan, Jingjing (Frontiers in Cellular Neuroscience, 2018)
NMDARs, the Ca2+ permeable channels, play central roles in synaptic plasticity, brain development, learning and memory. NMDAR binding partners and associated signaling has been extensively studied in synapse-to-nucleus communications. However, whether NMDARs could directly regulate synapse-to-nucleus communications is largely unknown. Here, we analyze the four alternative splicing of the C-terminus isoforms of GluN1 (1a, 2a, 3a, and 4a), and find that C1 domain of GluN1 is necessary for nuclear localization. Besides, we find that the 10 basic amino acids in C1 domain determine the nuclear localization of GluN1 C-terminus. Further investigating the expression patterns of the full length of GluN1 four isoforms shows that only GluN-1a exhibits the cytoplasmic and nucleus distribution in primary hippocampal neurons. Electrophysiological analyses also show that over-expression of GluN1 C-terminus without C1 domain doesn't affect synaptic transmission, whereas GluN1 C-terminus containing C1 domain potentiates NMDAR-mediated synaptic transmission. Our data suggested that the 10 basic amino acids in C1 domain determine translocation of GluN1 C-terminus into nucleus and regulate synaptic transmission.